Outcomes in Patients with Left Bundle Branch Block after Rapid Deployment Aortic Valve Replacement - Schlömicher, Markus; Useini, Dritan; Haldenwang, Peter Lukas; Naraghi, Hamid; Moustafine, Vadim; Bechtel, Matthias; Strauch, Justus Thomas (The Thoracic and Cardiovascular Surgeon, 2022)
Objectives Increased rates of postoperative left bundle branch block (LBBB) and permanent pacemaker implantation (PPI) frequently occur after implantation of rapid deployment valves. The impact of LBBB on follow-up outcomes remains controversial. So far, no data regarding long-term outcomes exist.Aim The aim of this study was to analyze the impact of LBBB on postoperative outcomes after rapid deployment aortic valve replacement (RDAVR).Methods A total of 620 consecutive patients without preexisting LBBB or PPI who underwent rapid deployment AVR between March 2012 and September 2019 were included. New-onset LBBB was defined as any new LBBB that persisted at hospital discharge. The median follow-up time for clinical data was 1.7 years post-RDAVR.Results At discharge, new-onset LBBB was seen in 109 patients (17.5%). There were no differences between the LBBB groups and no-LBBB groups regarding baseline characteristics. At a median follow-up of 1.7 years, no difference was found between LBBB groups and no-LBBB groups concerning all-cause mortality (12.8 vs. 11.7%; hazard ratio [HR]: 1.08; 95% confidence interval [CI]: 0.74–1.53; p = 0.54). Nevertheless, new-onset LBBB was associated with significant higher pacemaker implantation rates at follow-up (10.1 vs. 6.3%; HR: 3.58; 95% CI: 1.89–6.81 p < 0.001).Conclusion After a median follow-up of 1.7 years, new-onset LBBB was not associated with increased mortality. Nevertheless, higher pacemaker implantation rates were observed in patients with new-onset LBBB after RDAVR.
Keywords: aortic valve replacement; rapid deployment valves; left bundle branch block